The role of an anesthesıst at the times of natural dısasters - Ezgi Erkiliç; Elvin Kesimci; Süleyman Kaya; Mustafa Aksoy (Global Journal of Anesthesiology - Peertechz Publications, 2020)
During disasters, anesthesiologists may play a main role. It is known that anesthesiologist is extremely effective and capable in the management emergency cases during disaster times. In times of disaster, the anesthetist should not get stuck in the operating room only, with his experiences of intensive care and emergency response. Anesthetic management of patients in disaster situations is full of challenges for the anesthetist.The role of anesthesiologist after disaster is important to handle a safe and ideal surgical condition. A limited number of anesthesiologists in developing countries work in disaster preparedness and disaster management.  In this review, we aimed to discuss the role and choices of anesthetists during disasters with examples.